Educate at the University from the Voices of Students: Guiding Educational Decisions: Educar en la universidad desde las voces de los estudiantes: decisiones pedagógicas orientadoras (2022)
This article presents an experience of university teaching based on the proposal of the Seminar of Educational Reality, belonging to the Education Sciences course of studies at the National University of the Northeast, Argentina. This course of studies is for teacher training for secondary and higher education, as well as for professional performance in public and private educational organizations. The fundamental pedagogical sense that guides the Seminar is to “look” at education beyond the school as a formal institutional organization, that is, the educational issue is not resolved exclusively in the field of the school. On the contrary, the school is the place of resonance of what happens in other external spaces and, as a social institution, it is crossed by social, cultural, historical, political, and economic problems, thus becoming a space for the projection of social, cultural and life possibilities. Thus, this paper will seek to highlight the value of the role of public education through the voices of Education Science students who attended the Seminar and worked on different aspects that are part of the educational reality: sexuality, diversity, feminisms, among others.